Comparison between Pycnoporus sanguineus and Oxyporus latemarginatus in delignifying kenaf chips. - Halis, Rasmina; Tan, Hui Rus; Ashaari, Zaidon; Mohamed, Rozi (2011)
Pre-treatment is an important tool in conversion of lignoceIlu1osic biomass to valuable products. Biological pretreatment using white rot fungi degrades lignin and also alters the ultrastructure of lignocellulosic biomass, thus the pretreatment increases the facility to convert polysaccharide into simple sugars. This study compared the ability to degrade lignin by p sanguincus, which is a known lignin degrading fungus, to another tropical basidiomycete Oxypoms latemarginalus FRIM 31 isolated from Malaysia forest. The fungi were sub-cultured for 6 days in PDA media, inoculated by spreading on kcnaf chips and incubated for 1, 2, 4, 8 and 16 weeks. Corn steep liquor was added to initiate and enhance hgal growth. Treated kenaf was subjected to microscopic observation using scanning electron microscope (SEh-1) and chemical analysis using TAPPI Standard Methods. SEM observations showed evidence of fungal colonization. When calculating weight loss, both white rot fungi yielded similar amounts of reduction. Cellulose, hemicelluloses, extractives and lignin contents in the treated kenaf chips were decreased. Our result showed that 0. latemarginatus FRIM 31 had a great ability in lignin degradation compared to P. sanguineus.